Proceedings of the International Graduate Research in Education Seminar iGREduc 2023 - Faculty of Educational Studies (Faculty of Educational Studies, 2023)
The International Graduate Research in Education Seminar (i-GREduc) 2023, held on 18 November 2023 and organized by the Faculty of Educational Studies, focused on the theme Critical Thinking and Problem-Solving: Empowering the Next Generation of Learners.